“Diseño de estrategias de economía circular para la gestión eficiente de residuos plásticos con la asociación de recicladores del cantón Latacunga” - Donoso Veliz, Anggie Pierina (2024)
This study was conducted in the San Buenaventura neighborhood at the Señor de la Paz Base Recyclers Association facilities, with the help of 20 recyclers. The study aimed to design Circular Economy strategies that enable efficient management of plastic waste while taking into account the local characteristics, including technical, social, economic, and cultural aspects. To achieve this objective, a qualitative study was carried out involving surveys, bibliographic analysis, and detailed observations. These methods provided a complete view of plastic waste management in the canton. The study results are presented through the analysis of strengths, opportunities, weaknesses, and threats in the management of plastic waste. Several strategies were identified to promote sustainability, including training in self-management, resilience, and sustainable practices. Transforming financial and technical limitations into economic opportunities and personal development was also identified as a key strategy. The use of recyclable materials, community support, and adaptation to regulatory changes are promoted to ensure sustainability. The Comprehensive Training Program was implemented, focusing on the central proposal of manufacturing keychains using plastic waste. This initiative received 100% acceptance by participating recyclers and has proven to be a positive strategy to generate additional income for recyclers. Based on the study results, it is concluded that current plastic waste management practices urgently need to address challenges such as the scarcity of resources and the lack of institutional support. To address the environmental and social challenges associated with plastic waste management, a comprehensive approach is needed that combines training, environmental education, and the application of Circular Economy principles.